PENGEMBANGAN OBYEK WISATA TAMAN AIR TLATAR KABUPATEN BOYOLALI - Anggraini, Pramita; Widowati, Nina; Maesaroh, Maesaroh (Journal of Public Policy and Management Review, 2024)
One of the tourist attractions in Boyolali Regency, namely the Tlatar Water Park, is a potential tourist attraction that, if managed well, can increase local revenue. The aim is to describe and analyze how tourism is developed in and to find out aspects of the development of the Tlatar Regency Water Park Tourist Attraction. Qualitative descriptive research methods, data collection techniques dobservation, interviews and documentation. Results of research in the field, Development of Tourist Attractions in the Tlatar Regency Water Park as a whole it's been going well. However, there are still several components that have not been developed properly. The components that have been well developed are the Attractions component, in the form of natural attractions and cultural attractions. Then another component that has been well developed, namely the amenity component in the tourism development process at Tlatar Water Park, Boyolali Regency, has been developed quite well. Most of the facilities are complete and adequate. The component that has not been well developed is the accessibility component where access itself is the main thing that is very important for tourists going to Tlatar tourist locations. And also the supporting facilities component. There needs to be activities such as performances or festivals which are held regularly at the Tlatar Water Park Tourism location. there are improvements to the road to the Umbul Tlatar tourist location, additional types of public transportation to make it easier for tourists to visit the Tlatar Water Park tourist location, there is a need for additional lodging accommodation for tourists